One Pot Synthesis and Antimicrobial Evaluation of Schiif Base 1,2,4-Triazole Derivatives - Kishore N. Koinkar, (International Journal of Scientific Research in Science and Technology, 2025)
The development of heterocyclic compounds with potent antimicrobial properties remains a crucial area of medicinal chemistry. In this study, a series of Schiff base derivatives incorporating the 1,2,4-triazole core were synthesized via a green, one-pot condensation approach using aromatic aldehydes and substituted 1,2,4-triazole derivatives under the solvent. The protocol offers high yields, operational simplicity. The synthesized compounds were characterized by IR, 1H-NMR, and Mass spectrometry. Their antimicrobial activity was assessed against Gram-positive bacteria (Staphylococcus aureus), Gram-negative bacteria (Escherichia coli), and fungal strains (Candida albicans and Aspergillus niger) using the agar well diffusion method. Several derivatives exhibited moderate to significant antimicrobial activity, highlighting the potential of Schiff base-triazole hybrids as promising lead structures for the development of new antimicrobial agents.
Keywords: Schiff base; Antimicrobial agents; Heterocyclic; triazoles